Balance springs for timekeeping movements

A three-alloy blend of Nb, Ti, and optionally Zr/Hf addresses production inefficiencies and thermoelastic challenges in spiral springs, ensuring high elastic limits and stability for timepieces.

JP7626534B2Active Publication Date: 2025-02-04NIVAROX FAR SA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022036788
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-16
Filing Date
2022-03-10
Publication Date
2025-02-04
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

Existing spiral springs for timepieces face challenges in achieving high elastic limits, stable performance, small cross section, and thermoelastic coefficient compatibility within ±10 ppm/°C, while traditional Nb-Ti alloys result in long production times and potential formation of fragile Martensite phases.

Method used

A new chemical composition using a three-alloy blend of Nb, Ti, and optionally Zr and/or Hf, with controlled proportions and heat treatment processes, to enhance production efficiency and thermoelastic properties.

Benefits of technology

The new alloy composition reduces production time, minimizes secondary errors, and maintains high elastic limits and thermoelastic stability, suitable for chronometer performance across varying temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626534000001
    Figure 0007626534000001
  • Figure 0007626534000002
    Figure 0007626534000002
  • Figure 0007626534000003
    Figure 0007626534000003
Patent Text Reader

Abstract

To provide a spiral spring with chemical composition that eliminates fragile phases and reduces production time.SOLUTION: The invention relates to a spiral spring intended to attach to a balance of a horological movement. The spiral spring is made of an alloy consisting of: Nb and Ti elements; at least one element selected from Zr and Hf; optionally at least one element selected from W and Mo; and optionally other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al. The content of Nb is 40 to 84 wt.%, the total content of Ti, Zr and Hf is 16 to 55 wt.%, each content of W and Mo is 0 to 2.5 wt.%, and the content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm with the total content of the trace elements less than or equal to 0.3 wt.%. The invention further relates to a method for manufacturing such a spiral spring.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spiral spring intended to equip the balance of a timepiece movement. The invention further relates to a method for manufacturing this balance spring. [Background technology]

[0002] In the manufacture of spiral springs for portable timepieces (e.g. wristwatches, pocket watches), - High elastic limit - Easy to produce, especially by drawing and rolling - Excellent fatigue resistance - Stable performance over time - Small cross section We are faced with seemingly irreconcilable constraints.

[0003] The alloy selected for the spiral spring must also have properties that ensure that a watch incorporating such a spiral spring maintains its chronometric performance when used at different temperatures. The thermoelastic coefficient (TEC) of the alloy is therefore very important. To create a chronometric oscillator with a CuBe or German silver balance, the thermoelastic coefficient must be within ±10 ppm / °C. The formula that relates the thermoelastic coefficient of the alloy to the expansion coefficient of the spiral spring (α) and the expansion coefficient of the balance (β) is as follows:

[0004]

number

[0005] where the variable M is the rate in s / d, the variable T is the temperature in °C, E is the Young's modulus of the spiral alloy, (1 / E)(dE / dT) is the thermoelastic coefficient of the spiral alloy, and the coefficient of expansion is °C. -1 It is represented as:

[0006] In practice, TC is calculated between 8°C and 38°C as follows:

[0007]

number

[0008] This value must be between -0.6 and +0.6s / d℃.

[0009] Spiral springs for portable watchmaking are known from the prior art binary Nb-Ti alloys. In these alloys the proportion of Ti is typically between 40 and 60% by weight, in particular 47% by weight. Adapting the deformation and heat treatment diagram, these spiral springs have a two-phase microstructure containing niobium in the β phase and titanium in the form of precipitations in the α phase. In the cold-worked alloy, the β phase has a strongly positive thermoelastic coefficient, and by the precipitation of the α phase, which has a strongly negative thermoelastic coefficient, the thermoelastic coefficient of this two-phase alloy can be brought close to zero, which is particularly favorable for TC.

[0010] However, there are some challenges when using binary Nb-Ti alloys in spiral springs.

[0011] One of the challenges with binary Nb-Ti alloys is related to the precipitation of titanium, which occurs after the winding step, mainly during the settling process. Indeed, the precipitation times are very long, for NbTi47 alloy the times range from 8 to 30 hours, with an average of about 20 hours. This results in very long production times.

[0012] Apart from the problem of long production times, too much titanium can lead to the formation of a brittle martensite phase, which makes the material difficult or impossible to deform and unsuitable for the manufacture of spiral springs. Thus, it is recommended not to include too much titanium in the alloy.

[0013] Currently, there is still a need to develop new chemical compositions that meet the various requirements of being free of brittle phases and shortening the production time for producing spiral springs. Summary of the Invention [Problem to be solved by the invention]

[0014] The present invention aims to propose a new chemical composition of a spiral spring that can solve the above problems. [Means for solving the problem]

[0015] In this context, the present invention relates to a spiral spring for a watch made of at least a ternary alloy based on niobium and titanium. According to the invention, Ti is partially replaced by Zr and / or Hf, which are also capable of forming α-phase precipitates. By partially replacing Ti by Zr and / or Hf, it is possible to accelerate the precipitation during setting and to shorten the production time.

[0016] In particular, the invention relates to a spiral spring intended to equip the balance of a timepiece movement, said spiral spring comprising: the elements Nb and Ti, and at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo, and - with other trace elements, if present, selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al and made of at least a ternary alloy consisting of - the Nb content is 40-84 wt.%; the total content of Ti, Zr and Hf is between 16 and 55% by weight, preferably the content of Ti is greater than or equal to the minimum content of 15% by weight, - The W and Mo contents are 0-2.5 wt.% each; The content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt % or less.

[0017] The invention further relates to a method for manufacturing this spiral spring of a watch, said method comprising the steps of: - making or providing a blank made of at least a ternary alloy; - subjecting the blank to a beta quench such that the titanium of the alloy is substantially in solid solution, contains niobium in the beta phase, and zirconium and / or hafnium are also substantially in solid solution; - subjecting said alloy to a series of deformation sequences followed by intermediate heat treatments; - winding to form a spiral spring; and - a final heat treatment step, also called fixing, The alloy is the elements Nb and Ti, and at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo; - with other trace elements, if present, selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al; - the Nb content is 40-84 wt.%; the total content of Ti, Zr and Hf is between 16 and 55% by weight, preferably the content of Ti is greater than or equal to the minimum content of 15% by weight, - The W and Mo contents are 0-2.5 wt.% each; The content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt % or less.

[0018] Preferably, the final heat treatment step for final precipitation of titanium, zirconium and / or hafnium is carried out at a holding temperature between 400° C. and 600° C. for a duration of 4 to 8 hours.

[0019] In addition to reducing settling time, partial replacement of titanium with zirconium can reduce secondary errors as explained below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention relates to a spiral spring for a watch made from a ternary alloy containing at least niobium, titanium and one or more additional elements.

[0021] According to the invention, the alloy comprises: the elements Nb and Ti, and at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo, and - if present, other trace elements selected from O, H, C, Ta, Fe, N, Ni, Si, Cu and Al; - the Nb content is 40-84 wt.%; - the total content of Ti, Zr and Hf is 16 to 55% by weight; - The W and Mo contents are 0-2.5 wt.% each; The content of each element selected from O, H, C, Ta, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt % or less.

[0022] Preferably, the Nb content is greater than 45% by weight, or even 50% by weight or more, in order to obtain a sufficient proportion of β-phase with a strongly positive thermoelastic coefficient, which is intended to be compensated by the negative thermoelastic coefficients of the α-phases of Ti, Zr and Hf.

[0023] Preferably, the Ti content is maintained above a minimum content of 15 wt.% because Ti is more economical than Zr and Hf, and Ti has the advantage of having a lower melting point than Zr and Hf, making it easier to mold.

[0024] The proportion of oxygen is 0.10% by weight or less of the total, and further 0.085% by weight or less of the total.

[0025] The proportion of hydrogen is 0.01% by weight or less of the total, particularly 0.0035% by weight or less of the total, and further particularly 0.0005% by weight or less of the total.

[0026] The carbon content is preferably 0.04% by weight or less, more preferably 0.020% by weight or less, and even more preferably 0.0175% by weight or less.

[0027] The proportion of tantalum is 0.10% by weight or less of the total.

[0028] The proportion of iron is 0.03% by weight or less of the total, particularly 0.025% by weight or less of the total, and further particularly 0.020% by weight or less of the total.

[0029] The nitrogen content is preferably 0.02% by weight or less, more preferably 0.015% by weight or less, and even more preferably 0.0075% by weight or less.

[0030] The proportion of nickel is 0.01% by weight or less of the total.

[0031] The proportion of silicon is 0.01% by weight or less of the total.

[0032] The copper content is 0.01% by weight or less of the total, and particularly 0.005% by weight or less of the total.

[0033] The proportion of aluminum is 0.01% by weight or less of the total.

[0034] According to the invention, Ti is partially replaced by Zr and / or Hf, which, like Ti, forms alpha precipitates and can accelerate the precipitation during fixing and therefore shorten the production time. Preferably, the total content of Zr and Hf is 1-40% by weight. Preferably, the total content of Zr and Hf is 5-25% by weight, more preferably 10-25% by weight, even more preferably 15-25% by weight.

[0035] Preferably, Ti is replaced by at least Zr. This reduces the secondary error, which is a measure of the curvature of the rate, which is generally approximated by a straight line passing through two points (8°C and 38°C). To show the effect of Ti and Zr on the secondary error, tests were carried out on binary alloys Nb-Ti with a Ti percentage of 47% by weight (NbTi47) and Nb-Zr with Zr percentages ranging from 0 to 70% by weight. The secondary error was measured at 23°C. The secondary error is the difference between the rate at 23°C and the straight line connecting the rates at 8°C and 38°C. For example, the rates at 8°C, 23°C and 38°C can be measured using a Witschi chronoscope type device.

[0036] Table 1 below shows the data for pure Nb, NbTi47 alloy and Nb-Zr alloy as a function of the weight percent of Zr. Pure Nb has a secondary error of -6.6 s / d at 23°C. The precipitation of Ti in the NbTi47 alloy compensates for the negative effect of Nb, but it rises excessively by positive values ​​reaching 4.5 s / d. On the other hand, the Nb-Zr alloy has a negative secondary error for Zr contents greater than 0 weight percent and even zero for Zr contents of 45 weight percent and above. Thus, the partial replacement of Ti by Zr in the ternary alloy makes it possible to compensate for the too strong positive effect of Ti on the secondary error. The addition of a few weight percent of Zr makes it possible to reduce the secondary error to values ​​closer to zero than in the binary NbTi47 alloy. Therefore, the Zr content is preferably at least 5 weight percent.

[0037] [Table 1]

[0038] The alloy may further contain W and Mo, each in a content of 0-2.5 wt. %, which increases the Young's modulus of the alloy, so that for a given torque of the spring the thickness of the spiral is reduced, making the spiral lighter.

[0039] Preferably, the spiral spring of the present invention has a multiphase microstructure including central cubic β-phase niobium and single α-phase titanium and zirconium and / or hafnium.

[0040] To obtain such a microstructure, the manufacturing method requires that the α-phase precipitation is finished by heat treatment when the spring is fixed. The manufacturing method comprises the following steps in sequence: - making or preparing a blank For example, the blank may be made by melting elements in an electric arc or electron gun furnace to form a billet or ingot that is hot forged, cold deformed, and heat treated between the deformation steps. the elements Nb and Ti, and at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo; - other trace elements, if present, selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al and made of at least a ternary alloy consisting of - the Nb content is 40-84 wt.%; - the total content of Ti, Zr and Hf is 16 to 55% by weight; - The W and Mo contents are 0-2.5 wt.% each; The content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt % or less. - subjecting the blank to a beta quench such that the titanium of the alloy is substantially in solid solution, the niobium is in the beta phase, and the zirconium and / or hafnium are also substantially in solid solution. - subjecting said alloy to a series of deformation sequences followed by intermediate heat treatments. Deformation here means deformation by drawing and / or rolling. In drawing, it may be necessary to use one or more dies, if necessary, in the same sequence or in a different sequence. Drawing is carried out until a wire of round cross section is obtained. Rolling can be carried out in the same deformation sequence as drawing or in a different sequence. Preferably, the last sequence carried out on the alloy is rolling, preferably with a rectangular profile matching the entrance section of the winding pin. - Winding to form a spiral spring - Final heat treatment step

[0041] In these combined deformation-heat treatment sequences, each deformation is performed with a given deformation amount between 1 and 5, which corresponds to the traditional formula 2ln(d0 / d), where d0 is the diameter of the final β-quench and d is the diameter of the cold worked wire. The global accumulation of deformations over the entire series of sequences results in a total deformation amount between 1 and 14. Each combined deformation-heat treatment sequence includes a heat treatment for the precipitation of the α-phases of Ti, Zr and / or Hf each time.

[0042] The beta quench, which precedes the deformation and heat treatment sequence, is a melting treatment carried out under vacuum at temperatures between 700°C and 1000°C for durations between 5 minutes and 2 hours, followed by cooling under gas.

[0043] Furthermore, the beta quench is a melt treatment lasting 1 hour at 800° C. under vacuum, followed by cooling under gas.

[0044] To return to the combined deformation-heat treatment sequence, the heat treatment is a precipitation treatment carried out at a temperature between 300°C and 700°C for a duration between 1h and 200h, in particular at a temperature between 400°C and 600°C for a duration between 3h and 30h.

[0045] In particular, the method includes a number of combined deformation-heat treatment sequences ranging from 1 to 5.

[0046] In particular, the first combined deformation-heat treatment sequence includes a first deformation treatment that reduces the cross section by at least 30%.

[0047] In particular, each of the combined deformation-heat treatment sequences which is not the first deformation treatment comprises one deformation treatment between two heat treatments and reduces the cross section by at least 25%.

[0048] In particular, after the alloy blank is produced and before the deformation-heat treatment sequence, in an additional step, a surface layer of a ductile material selected from copper, nickel, cupro-nickel, cupro-manganese, gold, silver, nickel-phosphorus (Ni-P) and nickel-boron (Ni-B) is added to the blank to facilitate its formation into a wire upon deformation, and after the deformation-heat treatment sequence or after the winding step, the layer of ductile material is removed from the wire, in particular by chemical attack.

[0049] Alternatively, a surface layer of ductile material is deposited to form a spiral spring whose pitch is not a multiple of the blade thickness. In another variation, a surface layer of ductile material is deposited to form a spring whose pitch is variable.

[0050] Thus, in certain timepiece applications, ductile material or copper is added at certain points to facilitate forming into a wire shape such that a thickness of 10-500 μm remains on the wire with a final diameter of 0.3-1 mm. A layer of ductile material or copper is removed from the wire, particularly by chemical attack, and it is rolled flat and then wound to produce the actual spring.

[0051] The installation of the ductile material or copper can be galvanic or mechanical, in which case it is a jacket or tube of ductile material or copper, which is fitted onto a large diameter alloy rod and then thinned during the deformation step of the composite rod.

[0052] The removal of the layer can be carried out by chemical attack, in particular with cyanide or acid, such as nitric acid, based solutions.

[0053] The final heat treatment is carried out at a temperature between 300°C and 700°C for a duration between 1 hour and 200 hours. In particular, said duration is between 3 hours and 30 hours at a temperature between 400°C and 600°C. Preferably, the temperature is held at 400°C to 600°C for a duration between 4 hours and 8 hours. During this final heat treatment, the precipitation of titanium and hafnium and / or zirconium in the α phase is completed.

[0054] By a suitable combination of a series of deformations and heat treatments, a very fine, in particular nanometer-scale, microstructure can be obtained, which contains β-niobium and α-phases of titanium and hafnium and / or zirconium. This alloy combines a very high elastic limit, at least greater than 500 MPa, with an elastic modulus of at least 100 GPa, preferably at least 110 GPa. This combination of properties is suitable for spiral springs. Moreover, this at least ternary niobium-titanium-hafnium and / or zirconium alloy according to the invention can be easily covered with a ductile material or copper, which greatly facilitates deformation by stretching.

[0055] This alloy has similar properties to "Elinvar" and has a thermoelastic coefficient of practically zero in the temperature range typically used in watchmaking, making it suitable for the manufacture of self-compensating spirals.

Claims

1. A spiral spring intended to equip the balance of a timepiece movement, said spiral spring comprising: Nb and Ti elements, and at least one element selected from Zr and Hf; Optionally, at least one element selected from W and Mo; and Other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu and Al; It is made of an alloy consisting of The Nb content is 50 to 80 wt. %; The total content of Ti, Zr and Hf is 20 to 40 wt. %; The contents of W and Mo are each 0 to 2.5 wt.%; The content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt% or less; The Ti content is 15% by weight or more. Spiral spring characterized by:

2. Contains Zr and Hf 2. The spiral spring according to claim 1 .

3. It has a microstructure containing Nb in the β phase, Ti in the α phase, and Zr and / or Hf.

3. The spiral spring according to claim 1 or 2.

4. The elastic limit is 500 MPa or more, and the elastic modulus is 100 GPa or more.

4. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

5. A method for manufacturing a spiral spring intended to equip the balance of a timepiece movement, comprising the steps of: Providing a blank with at least a ternary alloy; subjecting the blank to a beta quench such that the titanium of the alloy is substantially in solid solution, the niobium is in the beta phase, and the zirconium and / or hafnium are also substantially in solid solution; subjecting the alloy to a series of deformation sequences followed by intermediate heat treatments; winding to form a spiral spring; and A final heat treatment step is performed. The alloy is Nb and Ti elements, and at least one element selected from Zr and Hf; Optionally, at least one element selected from W and Mo; and other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, and Al; The Nb content is 50 to 80 wt. %; The total content of Ti, Zr and Hf is 20 to 40 wt. %; The contents of W and Mo are each 0 to 2.5 wt.%; The content of each element selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, and Al is 0 to 1600 ppm, the total content of the trace elements is 0.3 wt% or less, and the content of Ti is 15 wt% or more. A method comprising:

6. The beta-quench is a melting treatment carried out under vacuum at temperatures between 700°C and 1000°C for a duration of 5 minutes to 2 hours, followed by cooling under gas.

6. The method of claim 5 .

7. The beta quench is a melting treatment at 800° C. under vacuum for a duration of 1 hour, followed by cooling under gas.

7. The method according to claim 5 or 6.

8. The final and intermediate heat treatments of each sequence are α-phase Ti, and Zr and / or Hf precipitation treatments at holding temperatures between 300° C. and 700° C. for durations between 1 hour and 200 hours. The method according to any one of claims 5 to 7.

9. The final heat treatment is carried out at a holding temperature of 400° C. to 600° C. for a duration of 4 to 8 hours. The method according to any one of claims 5 to 8.

10. After the step of providing the alloy blank and before the steps of performing the series of deformation sequences and then performing intermediate heat treatments, adding a surface layer of a ductile material selected from copper, nickel, cupro-nickel, cupro-manganese, gold, silver, nickel-phosphorus (Ni-P) and nickel-boron (Ni-B) to the blank to facilitate forming into a wire shape; removing the layer of ductile material by chemical attack before or after the winding to form a spiral spring; The method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Self-compensated hair spring and its production

    JP1999071625A

  • Balance spring for timepiece movements and method for manufacturing the same

    JP2019113544A

  • Method for manufacturing balance spring for horological movement

    JP2020183940A

  • Metastable beta titanium alloy, watch spring based on this alloy, and method for its manufacture

    JP2020515720A